If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -3 = -5x + 4 Reorder the terms: -3 + -4x = -5x + 4 Reorder the terms: -3 + -4x = 4 + -5x Solving -3 + -4x = 4 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -3 + -4x + 5x = 4 + -5x + 5x Combine like terms: -4x + 5x = 1x -3 + 1x = 4 + -5x + 5x Combine like terms: -5x + 5x = 0 -3 + 1x = 4 + 0 -3 + 1x = 4 Add '3' to each side of the equation. -3 + 3 + 1x = 4 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 4 + 3 1x = 4 + 3 Combine like terms: 4 + 3 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| 16.24/0.14=116 | | 6y+14+7=y+2y-13 | | n+215=x | | c-5.3=-6.3 | | 2*z-31=-9*z+24 | | 6x+1=4n+19 | | 20/5=4 | | 6=2[y+2] | | (11)-(-3)= | | -6-9x-13=-246 | | 45=35-y | | -6+3v=15 | | 0=(5x^2)+5x-42 | | .25(19-y)+.10y=3.70 | | -6+6v=7(5v-5) | | xr-sx+y=z | | (-7)-(-20)= | | -4x+8=-36 | | 285.7*0.75= | | (80x+120)-(13x+50)=0 | | -3(7y-2)-(5y+9)= | | 2x+25=14-6x | | rx-sx+y=z | | 15=9n-6 | | b-23=51 | | (8)-(-9)= | | 4+(-4g)=16 | | 8(6x-4)= | | 8x+30=-61+x | | 2(-3n+4)=-3(6+2n) | | 12=t-12 | | 5+3(x-2)=19 |